Synthesis, characterization and biological docking simulation of new thiophosphoric triamide (S)P[NH-2Py-(5-CH3)]3 and its Cu(II) complex - Atekeh Tarahhomi; Zeinab Albobaledi (Results in Chemistry, 2025)
New thiophosphoric triamide (S)P[NH-2Py-(5-CH3)]3 (PS) and its corresponding Cu(II) complex were synthesized and characterized using CHN elemental analysis, UV–Visible and FT-IR spectroscopies. The structure of PS was experimentally investigated by single crystal X-ray diffraction. PS crystallizes in the triclinic crystal system, space group P1¯, with one independent molecule in the asymmetric unit. The hydrogen bonding pattern in the PS structure involves a centrosymmetric dimer formed through classical NH…N hydrogen bond interactions. For the Cu(II) complex, the proposed structure consists of two tridentate O,N,N-donor amidothiophosphate ligands (S)P[O−][NH-2Py-(5-CH3)]2. The Cu(II) center adopts an octahedral geometry with a six-coordinate Cu(N)4(O)2 environment. For a biological evaluation, molecular docking simulations were conducted on both PS and its Cu(II) complex against target proteins of DNA, SARS-CoV-2 and Monkeypox (Mpox) providing maximum binding energies of −8.2, −7.5 and − 7.2 kcal/mol, respectively, for PS. These results suggest that the compounds studied, particularly PS, possess considerable potential as inhibitors of DNA and viral targets, with docking affinities comparable to those of established anticancer and antiviral drugs. This makes them promising candidates for further therapeutic investigation.